TINGKAT PENGETAHUAN TENTANG CARA MEMELIHARA KESEHATAN GIGI DAN MULUT DENGAN KEJADIAN GINGIVITIS MASA PUBERTAS PADA SISWA KELAS VII A SMP NEGERI 8 MANADO - Mustapa Bidjuni; I Ketut Harapan; Ni Luh Rizky Astiti (Jurnal Kesehatan Gigi (Dental Health Journal), 2023)
A person's knowledge influences oral health maintaining. Lack of dental health knowledge causes a person to ignore dental and oral health problem which often occuring dental problems, such as gum inflammation (gingivitis). Gingivitis is an inflammation of the gingiva caused by plaque. Gingivitis can also occur due to changes in hormonal factors such as during puberty. Based on the results of the 2018 Basic Health Research, the proportion of dental and oral health problems in Indonesia was 57.6%, with characteristics of gingival/swollen gums of 14.0% and characteristics of gingival/bleeding gums of 13.9%. In North Sulawesi, the cases of gingiva/gums with swelling was 18.2% and gingiva/gums with bleeding was 20.4%.  Objective: The purpose of the study was to determine the relationship between the level of knowledge on maintaining oral health and the incidence of gingivitis during puberty in students. Methods: This type of research is an analytical survey with a cross sectional study approach. This research was conducted in May 2022 located at 8 State Junior High School Manado. The research sample was 40 people, the research instrument used were a structured questionnaire, set diagnosis, periodontal probe and format gingival index. The data obtained were analyzed using the product moment correlation statistic test. Result:   the result is p=value 0.144 ( 0.05 ) and r count = -0.235 r table 0.320). The conclusion is that there is no correlation between the level of knowledge about maintaining oral health and the incidence of gingivitis during puberty.